Vaccine inequity: a threat to Africa’s recovery from COVID-19 - Calvin R. Wei; Samuel Kamande; Godwin C. Lang’at (Tropical Medicine and Health, 2023)
Abstract Background Vaccine inequity is a reality facing the Sub-Saharan Africa region as vaccine nationalism from high-income countries (HICs) leads to limited access to the lifesaving vaccines needed to end the pandemic. In Africa, a significant portion of the population has yet to be vaccinated against Covid-19; however, the barriers to accessing such vaccines, including capacity challenges, still persist despite the implementation of the COVAX facility meant to support the lower- and middle-income countries (LMICs) to boost vaccination. Methods This study involved a systemic narrative review where literature search was conducted using the NCBI’s PMC and BMC databases based on defined keywords. Three authors were involved in the literature search and consensus was applied to settle disagreements and validate the findings. Results In this systematic narrative review, we report that vaccine nationalism remains a challenge for LMICs as HICs still hoard vaccines and even bypass COVAX to procure doses directly from the manufacturers. Factors that promote vaccine hesitancy in Africa include misinformation regarding the Covid-19 vaccine, a lack of trust in politicians and the pharmaceutical industry, and concerns about vaccine safety and efficacy. The policies implemented to enhance vaccine coverage in Africa, such as mandates, community engagement, and partnerships, all seek to promote equity of vaccination and ending Covid-19. Conclusion Covid-19 vaccine inequity persists and contributes to prolonged pandemic in LMICs. In response, African governments have taken certain measures to enhance vaccine uptake but more needs to be done to address resistance to vaccines.